2021
DOI: 10.7759/cureus.14620
|View full text |Cite
|
Sign up to set email alerts
|

Use of Early-Onset Sepsis Risk Calculator for Neonates ≥ 34 Weeks in a Large Tertiary Neonatal Centre, Saudi Arabia

Abstract: Early-onset sepsis (EOS) refers to sepsis with onset before 72 hours of life. Kaiser Permanente Calculator (KPC) or EOS risk calculator is an advanced multivariate risk model for predicting EOS in infants. ObjectiveTo examine the EOS risk calculator effect for predicting neonatal EOS, the necessity for laboratory tests, antibiotic usage, and length of hospital stay among the term and late-preterm newborns. MethodIn this cross-sectional study, we evaluated 44 cases of neonates ≥34 weeks of gestation started on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…SRC implementation would also lead to fewer NICU admissions, decreased length of stay in the NICU, and fewer laboratory tests. 13 In our study, the SRC recommended antibiotic management in 15 patients (0.5%) and only 2 patients had positive blood cultures. The number of patients recommended for antibiotics by the SRC was low, thus minimizing the exposure to antibiotics without missing a case of sepsis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…SRC implementation would also lead to fewer NICU admissions, decreased length of stay in the NICU, and fewer laboratory tests. 13 In our study, the SRC recommended antibiotic management in 15 patients (0.5%) and only 2 patients had positive blood cultures. The number of patients recommended for antibiotics by the SRC was low, thus minimizing the exposure to antibiotics without missing a case of sepsis.…”
Section: Discussionmentioning
confidence: 58%
“…Several studies evaluated the calculator's safety in different countries and populations, permitting it to be a tool for proper neonatal antibiotics stewardship. 11 These studies have included Germany, 6 the United Kingdom, 12 Saudi Arabia, 13 the Netherlands, and Australia. 11 As of yet, use of the SRC has not been studied or validated in the Lebanese population.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not expected to be superior in terms of antibiotic optimisation. 20 Sepsis risk calculators are infrequently employed in many regions of the world, and this is in part because they have not been validated in these contexts so clinicians are reluctant to make decisions using them. Here, we suggest a pragmatic use of such a calculator, focusing just on well-appearing infants as a way of introducing the concept to new clinicians and lowering the barriers to use the SRC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GBS screening for pregnant women is not a standard of care in Saudi Arabia yet ( 16 ). A recent cohort study identified the risk for early NS in Saudi Arabia to be 0.5/1,000 live births ( 17 ). A unified management plan of at-risk neonates can help further reduce the risk of complications posed by having an early neonatal infection ( 18 ).…”
Section: Introductionmentioning
confidence: 99%